EXPERIMENTAL STUDY AND ANALYSIS OF FLAT PLATE SOLAR WATER HEATER WITH PUMP - Shukla, Anupras; Singh, Pushpraj (International Journal of Engineering Technologies and Management Research, 2017)
In this study, we are achieving the hot water from solar water heater. The solar water heater are archiving the solar radiation from sun energy after that we are obtaining the hot water, in this way we are obtained the various temperatures of hot water with the help of circulating pump, the pump are used for obtaining the various flow rate of using water. The solar water heater is having several parts such as collector, pipe, water container and pump.